ASSESSING PROFESSIONAL COMPETENCIES AMONG COLLEGE TEACHERS ACCORDING TO THE PROFESSIONAL STANDARD: A CASE STUDY IN KAZAKHSTAN - Сапиева, Майра; RAIMBEKOVA, Zh.; SURTUBAEVA, D.; NABATNIKOVA, T.; TOREBEKOVA, A. (Pedagogy and Psychology, 2024)
This article presents findings from a comprehensive study aimed at evaluating the professional competencies of college teachers in accordance with the Professional Standard «Teacher». The study's objective was to investigate the current status of professional competency development among college educators and to formulate recommendations for their ongoing professional growth. A total of 342 respondents from 18 educational institutions in the Karaganda, Kostanay, and Zhambyl regions, encompassing both urban and rural settings, participated in the study. This diverse sample included 36 teachers from six self-assessment colleges, as well as representatives from administration, colleagues, and students. The results of the study facilitated the identification of «risk zones» in the development of professional competencies among college teachers, along with a nuanced understanding of the characteristics associated with both low and high competency indicators, as outlined by the Professional Standard «Teacher». Drawing upon these findings, recommendations were formulated to enhance the system of continuous professional development for college educators.